A rattle of bones eaudiobook - Skelton, Douglas (Rebecca Connolly, 2022)
When banners proclaiming the innocence of James Stewart spring up at the gravesite of his famous namesake-a clan leader who was falsely accused of murder and hanged almost three hundred years ago in a miscarriage of justice that still resonates-investigative reporter Rebecca Connolly smells a story. The publicity stunt was clearly meant to draw attention, but what's behind it and why now? The young Stewart has been in prison for ten years for the brutal murder of his lover, lawyer and politician Murdo Maxwell, in his home in Appin, near the site of the Stewart monument. Rebecca soon discovers that, prior to his murder, Maxwell believed he was being followed, and his phones were tapped. What would justify a government phone tap against a public figure? And why is a Glasgow crime boss so interested? As Rebecca keeps digging, she finds herself in the sights of Inverness crime matriarch Mo Burke, who wants payback for the damage caused to her family in a previous case. Set against the stunning backdrop of the Scottish Highlands, A Rattle of Bones is a tale of injustice and mystery, and the enduring echo of the past in the present.